Biographical Life Course Research Studying the Biography-History Dynamic - Nilsen, Ann.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
(3z(BBiographical Life Course Research provides a fascinating comparative/historical account of the theoretical and methodological underpinnings of life course study, from the Chicago School to contemporary debates surrounding structure and agency, postmodern individualism, and the (3z(Bcultural turn(3y (Bin biographical research. Insightfully, Ann Nilsen details how growing recognition of the gendered character of life courses has enhanced understanding of history and biography.(3y $1 (BJeylan Mortimer, University of Minnesota, USA (3z(BThis is the ideal volume for teaching biographical and life course research methods and will be essential reading for students wishing to use this powerful approach in their own studies. It provides a blueprint for how we might forge better connections between qualitative and quantitative approaches to research, using biographical methods to address the great challenges of our times including growing inequality and climate disaster.(3y $1 (BRachel Thomson, University of Sussex, UK This open access book explores an approach that connects individual and societal processes throughout history and shifting trends in sociological perspectives, influenced by C. Wright Mills$1 (Btheories of time and temporality. It traces its origins from American pragmatist thought and Chicago qualitative sociology in the early 20th century to the revival of biographical research in European and American sociology during the 1970s. The book shows empirical studies from this vibrant research approach can bridge methodological gaps between qualitative and quantitative biographical studies, applicable to various topics like class, gender, ethnicity, and intergenerational dimensions. Ann Nilsen is Professor of Sociology at the University of Bergen, Norway. She has been a visiting Professor at the University of Uppsala, Sweden, and University College London, UK. The biographical life course approach has been the methodological basis of her empirical research, published in books and articles. .s
Chapter 1 Life Course Studies and Biographical Research: Exploring the Individual-Society Relationship -- Chapter 2 The origins of Biographical and Life Course Research -- Chapter 3 The Revival of Biographical Research in Europe and America -- Chapter 4 Time and Temporality in Biographical Life Course Research -- Chapter 5 The Future as a Topic in Biographical Life Course Approaches -- Chapter 6 Methodological and Other Controversies -- Chapter 7 Reflections.
Keywords: Sociology -- Methodology; Human geography; Sociology; Social groups; Language and languages -- Style; Sociological Methods; Human Geography; Sociology of Family, Youth and Aging; Stylistics